Concerns of Female Adolescents About Menarche and First Sexual Intercourse: Mixed Methods Analysis of Social Media Questions - Yom-Tov, Elad (JMIR Pediatrics and Parenting, 2019)
Background: Adolescents use social media for information on medical and social aspects of maturation. Objective: The aim of this study was to investigate the concerns and information needs of adolescents regarding menarche and first sexual intercourse. Methods: Questions about menarche or first sexual intercourse were obtained from Yahoo Answers, a community-based social media question-and-answer website. A total of 1226 questions were analyzed. We focused on 123 question pairs made by users who asked questions on both topics and reported their ages at each. Quantitative and qualitative analyses were performed on these question pairs. Results: Qualitative analysis identified uncertainty as a significant theme for both menarche and first intercourse. Quantitative analysis showed that uncertainty was expressed in 26% (13/50) of menarche questions and 14% (7/50) of intercourse questions. Lack of communication was expressed in 4% (2/50) of menarche questions, compared with 8% (4/50) of intercourse questions. Ages at menarche and at first sexual intercourse were correlated, with women reporting menarche at the age of 13 years or younger being 2.6 times more likely to experience first sexual intercourse before the age of 16 years (P<.001, chi-square test). Older age at menarche was associated with greater lack of communication with parents (analysis of variance, P=.002). Conclusions: The questions of adolescents on the topics of menarche and first sexual intercourse express anxiety and uncertainty and are associated with a lack of information and deficient communication with parents. The more normative and expected a behavior, the less these factors appear. Therefore, parents and educators should, to the extent possible, improve communication around these topics, especially when they occur at less typical ages.